Phytochemical Screening and In Vitro Antibacterial Activity of Green Tea (Camellia Sinensis L) Extract Against Staphylococcus Epidermidis - Hardian Bimanto; Yuyun Dwi Wahyuni; Diah Titik Mutiarawati; Lully Hanni Endarini (Health Notions, 2020)
This study aimed to determine phytochemical screening and ethanol extract activity of the green leaves against Staphylococcus epidermidis. The microbial activity of the ethanol extract was carried out using the diffusion and dilution method with concentrations used of 1.5%, 2.5%, 3.5%, 4.5%, and 5.5% accompanied by three repetitions. The results showed that the ethanol extract of green tea leaves contained alkaloids, saponins, steroids or triterpenoids, flavonoids, polyphenols, and tannins and had the largest inhibition zone diameter of 30mm at a concentration of 4.5%. KHM (Minimum Inhibitory Content) at a level of 4.5% and KBM (Minimum Kill Rate) at a concentration of 5.5%. Analysis of the data with the normality test then proceed with the Kruskal Wallis test obtained a value of P = 0.008. With the value P